2019
DOI: 10.1002/open.201900146
|View full text |Cite
|
Sign up to set email alerts
|

Laccase Encapsulation in ZIF‐8 Metal‐Organic Framework Shows Stability Enhancement and Substrate Selectivity

Abstract: CgL1 laccase from Corynebacterium glutamicum was encapsulated into the metal‐organic framework (MOF) ZIF‐8 which was synthesized in a rapid enzyme friendly aqueous synthesis, the fastest in situ encapsulation of laccases reported to date. The obtained enzyme/MOF, i. e. laccase@ZIF‐8 composite showed enhanced thermal (up to 70 °C) and chemical (N,N‐dimethylformamide) stability, resulting in a stable heterogenous catalyst, suitable for high temperature reactions in organic solvents. Furthermore, the defined stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…SEM showed that GOx@ZIF‐8 was smaller than ALP@ZIF‐8 in particle size. The shape of these composites was similar to those reported in some studies [15,18,24] but different from the polyhedral shape reported in others [5,7,8] . The variations in morphology ( e. g .…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…SEM showed that GOx@ZIF‐8 was smaller than ALP@ZIF‐8 in particle size. The shape of these composites was similar to those reported in some studies [15,18,24] but different from the polyhedral shape reported in others [5,7,8] . The variations in morphology ( e. g .…”
Section: Resultssupporting
confidence: 70%
“…It is therefore likely that the susceptibility of enzyme@ZIF‐8 composites to these chemical agents is not greatly affected by the exact nature of the proteins in the composites. However, the morphology, particle size and crystallinity of the enzyme@ZIF‐8 composites do appear to vary among studies even under similar synthesis conditions [5,7,8,15,18,24] and surface area of lipase@ZIF‐8 is affected by the Zn 2+ /2‐MI molar ratio during synthesis [61] . It is likely that these properties ( i. e .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…There are hundreds of existing ZIFs [ 26 ], ZIF-8 (Zn(mIm) 2 , mIm = 2-methylimidazolate), which is the most common and widely investigated ZIFs [ 27 ]. The method to synthesize laccase@ZIF-8 composite has been reported in some literature [ [28] , [29] , [30] , [31] ]. ZIF-67 (Co(mIm) 2 , mIm = 2-methylimidazolate), which is also the most representative ZIF materials with a zeolite sod topology [ 32 ].…”
Section: Intorductionmentioning
confidence: 99%